Penerapan Model Pembelajaran Project Based Learning (PjBL) untuk Meningkatkan Kreativitas pada Pembelajaran IPAS Siswa Kelas IV SDN 02 Tebaban - Mita Juliana; Najmul Hadi; Farhana Muhammad (Lembaga Bale Literasi, 2023)
Based on the results of previous observations, it is known that the low level of student creativity and the application of learning models that are not appropriate for subjects IPAS. This study aims to determine the application of the PjBL model in learning IPAS with a focus on making maps and Pop Up Book media for Indonesian cultural diversity, and how this model can increase the creativity of fourth grade students at SDN 02 Tebaban. The research method used in this study was classroom action research (CAR) in class IV with a total of 18 students. The data collection technique used was a test using a rubric for assessing student creativity. The data analysis used was descriptive qualitative analysis and descriptive statistical data analysis. Qualitative descriptive analysis techniques are used to analyze data in the form of information in the form of sentences. Meanwhile, descriptive statistical data analysis is used to analyze quantitative data in the form of numbers, namely from the assessment of student creativity. Based on the results of data analysis obtained by the creativity of students in the first cycle, the score was 77.8% in the creative category and increased in the second cycle, which was 88.9% in the very creative category. Thus, the project based learning model can increase the creativity of students at SDN 02 Tebaban.